Jejunal metastases of a lobular carcinoma of the breast - Puñal, Alicia; Maglione, Oscar; Cazabán, Luis; Pressa, Carlos (Cirugía del Uruguay, 2004)
Breast cancer has a high mortality index in our country; metastatic diseases is the main condition responsible for deaths. The paper deals with the clinical case of a patient suffering from Jejunal metastases of a lobular adenocarcinoma of mamma, in which both made their appearance concomitantly. sive intestinal condition requiring urgency surgical treatment invo/ving a jejunal tumor resection. Ouring the same hospita/isation period, a breast nodu/ e of undetermined cancerous cyto/ogy was punctured. The study was discontinued and this undoubted/ y contributed to the initial diagnostic error of intestinal carcinoid tumor This secondary effect had the aspect of an occlu